Same Involvement, Different Reasons: How Personality Factors and Organizations Contribute to Heavy Work Investment - Mazzetti, Greta (Int J Environ Res Public Health, 2020)
The academic literature has drawn a clear distinction between a positive form (i.e., work engagement) and a negative form (i.e., workaholism) of heavy work investment (HWI). Nevertheless, the different weight of individual and situational factors contributing to their development was not thoroughly explored. This study aims to investigate the role of individual variables (i.e., obsessive–compulsive traits, achievement orientation, perfectionism, and conscientiousness) and situational factors (i.e., job demands and overwork climate) regarding engagement and workaholism simultaneously. Hypotheses were tested using a sample of 523 Italian employees. Results of structural equation modeling revealed that overwork climate and job demands were conversely related to engagement and workaholism, with job demand reporting the strongest association with workaholism. Furthermore, fear of failure was the only individual factor showing a significant and opposite relationship with workaholism and engagement. In contrast, perfectionism was positively associated with both forms of HWI. These results shed light on the potential effectiveness of intervention strategies focused on the employees and organizations in preventing workaholism and promoting engagement.